Low-Temperature ZnO Thin Film and Its Application in PbS Quantum Dot Solar Cells - Mai, Xuan Dung (H. : ĐHQGHN, 2018)
Zinc oxide (ZnO) has been widely deployed as electron conducting layer inemerging photovoltaics including quantum dot, perovskite and organic solar cells. Reducing the curing temperature of ZnO layer to below 200 oC is an essential requirement to reduce the cell fabrication cost enabled by large-scale processes such as ink-jet printing, spin coating or roll-roll printing. Herein, we present a novel water-based ZnO precursor stabilized with labile NH3, which allow us to spin coat crystalline ZnO thin films with temperatures below 200 oC. Thin film transistors (TFTs) and diode-type quantum dot solar cells (QD SCs) were fabricated using ZnO as electron conduction layer. In the QD SCs, a p-type 1,2 ethylenedithiol treated PbS QDs with a bandgap of 1.4 eV was spin-coated on top of ZnO layer by a layer-by-layer solid state ligand exchange process. Electron mobility of ZnO was about 0.1 cm2V-1s-1as determined from TFT measurements. Power conversion efficiency of solar cells: FTO/ZnO/PbS/Au-Ag was 3.0% under AM1.5 irradiation conditions. The possibility of deposition of ZnO at low temperatures demonstrated herein is of important for solution processed electronic and optoelectronic devices.